Regulation of Muscle Contraction and How Mutations in the Muscle Proteins Cause Heart Disease: The Laboratory Techniques Involves Molecular Biology, Protein Expression, Purification and Characterization Using Biochemical and Biophyisical Techniques - Maluze, Ugochukwu Obinna (British Journal of Healthcare and Medical Research, 2024)
The expansion of the causative mutations to the rigid thin filament changed the description of hypertrophic cardiomyopathy (HCM) from an illness of the cardiac motor to a syndrome of the cardiac sarcomere and significantly extended the gasp of the potential molecular pathogenic mechanism. An interesting hypotheses concerning disease mechanism posted that the diverse medical prognoses in the familial type of HCM may possibly be related to mutations in self-regulating protein machinery of the sarcomere (Frank et al, 1968). The journal of the novel study in 1990 establishes the inherited association of the beta-myosin and tropomyosin heavy chain genetic material to familial type of hypertrophic cardiomyopathy (HCM). The current studies conducted by some researchers elaborated on the various genetic alterations inside the genes encoding for the sarcomeric cardiac proteins, alpha tropomyosin, troponin T, and myosin protein components. The regularity of gene alteration in the alpha tropomyosin protein (TPM1) is lesser, contributing to 5% of FHC. Currently, the D175N gene mutation has been recognized in various unrelated populations, signifying that this spot could be an abnormal gene “hot spot” for the disease. In this project research, a wild type of normal protein and mutant genetic proteins (E180G and D175N) which are clinically involved in familial hyper cardiomyopathy (FHCM) were produced. Having in mind that the main effect of mutations E180G and D175N are mainly related to the thermal stability of the protein; this research will also investigate the differences between the thermal stability of wild type and mutated protein types using a Dye base fluorescent method of analysis. Dye based fluorescent method was used to monitor protein folding as a function of temperature for wild type tropomyosin and for HCM mutant E180G and D175N proteins. The column chromatography method of purification was used to purify the wild type and mutated proteins, and the protein bands were separated using gel electrophoresis methods. A similar assessment of folding stability and structural reports of several authors was in consistency with this present report which suggested that such mutations might alter protein folding. The results agree with previously published reports on the impaired function of expressed E180G and D175N mutations suggesting that the biochemical defects of the motor domain may affect myosin filament assembly in the sarcomere. For future prospects, future biochemical analysis of several other FHC mutations will be needed to establish a definite correlation between the enzymatic impairment between different mutants and their clinical phenotype of heart disease.